Numerical and observational investigations of long-lived, MCS-induced, severe surface wind events: the derecho - Schmidt, Jerome M., author (Colorado State University. Libraries, 1991)
This study addresses the production of sustained, straight-line, severe surface winds associated with mesoscale convective systems (MCSs) of extratropical origin otherwise known as derechos. Derechos are particularly violent summertime systems capable of producing a swath of damaging outflow winds and/ or severe wind gusts(> 25 m s-1 ) having a major axis of at least 400 km in length. Climatological data compiled for several derechos in the United States have shown that they typically occur in the upper Midwest, have average propagation speeds of 24 m s-1 , average lifetimes of 9 hours, and typically form in environments characterized by strong static stability within the lowest few kilometers of the atmosphere. In this dissertation the physical processes which govern the observed derecho characteristics are identified and their possible forcing mechanisms are determined. To address these problems, detailed observations of two derechos are presented along with simulations using the Colorado State University Regional Atmospheric Modeling System (CSU-RAMS). The observations revealed a derecho environment characterized by strong vertical wind shear through the depth of the troposphere and large values of convective available potential energy (CAPE). The thermodynamic environment of the troposphere in each case had a distinct three-layer structure consisting of: (i) a surface-based stable layer of 1- o-2 km in depth , (ii) an elevated well-mixed layer of 2-4 km in depth, and (iii) an upper tropospheric layer of intermediate stability that extended to the tropopause. Note that this profile is in stark contrast to the neutral subcloud layer which typifies the downburst environment. This suggests that mechanisms other than strong penetrating downdrafts may be responsible for the severe surface winds. Two primary sets of simulations were performed to assess the impact of the observed environmental profiles on the derecho structure, propagation, and longevity. The first set consisted of nested-grid regional-scale simulations initialized from the standard NMC analyses on a domain having relatively coarse horizontal resolution (75 km). These simulations were useful for identifying features of the regional-scale environment which affected the derecho longevity and track. They also provided further insight into the temporal and spatial characteristics of observed environmental features, such as the nocturnal low-level jet and static stability profiles. The second set of simulations consisted of two and three-dimensional experiments initialized in a horizontally homogeneous environment having a relatively fine horizontal resolution (2 km) and explicit microphysics. These experiments were particularly useful for depicting the convective and mesoB-scale (20-200 km) aspects of the simulated MCS which impacted the severe surface wind development, system longevity, and propagation characteristics. The results from these experiments indicate the importance of convectively-induced gravity waves on the MCS structure, propagation, longevity, and severe surface wind development. The sensitivity of the simulated convection and gravity waves to variations in the vertical wind shear and moisture profiles are described. Finally, observations of derechos reveal their convective structure typically consists of bow echo squall lines. Detailed Doppler radar analyses and 3-D simulations of a severe, bow echo squall line are presented which reveal the unique 3-D circulation features which accompany these mesoscale convective systems. We will illustrate how the mesoscale and convective-scale flow fields within the bow echo establish the severe surface wind maximum which is often located within the vertex region of the bow echo.
March 27, 1991.
Also issued as author's dissertation (Ph.D.) -- Colorado State University, 1991.
Keywords: Mesometeorology; Convection (Meteorology); Convective clouds; Thunderstorms